Penegakan Hukum terhadap Tindak Pidana Narkotika Berdasarkan UU No. 35 Tahun 2009 dan Pedoman Jaksa Agung No. 11 Tahun 2021 [Law Enforcement Against Narcotics Crimes Based on Law No. 35 of 2009 and the Attorney General's Guidelines No. 11 of 2021] - Aryadi Almau Dudy; Suheflihusnaini Ashady; Ahwan Ahwan (Indonesia Berdaya, 2026)
Law enforcement against narcotic crimes in Indonesia requires a proportional and layered approach. Based on Law No. 35 of 2009 and the Attorney General’s Guideline No. 11 of 2021, the enforcement system is built on a differentiation of offenders, whereby users, addicts, and victims of drug abuse are directed toward rehabilitative mechanisms, while dealers, manufacturers, couriers, and network actors are subjected to a repressive approach. The Integrated Assessment serves as a key instrument to determine the legal and medical status of the offender, preventing excessive criminalization and ensuring an appropriate legal response. This study demonstrates that the effectiveness of law enforcement depends heavily on consistent implementation of assessments, the professionalism of law enforcement officers, and cross-agency coordination. In conclusion, Indonesia’s narcotics law enforcement model integrates human rights protection, substantive justice, and firm action against drug trafficking, while positioning the assessment as the primary filter in determining the case handling pathway. Abstrak. Penegakan hukum terhadap tindak pidana narkotika di Indonesia menuntut pendekatan yang proporsional dan berlapis. Berdasarkan UU No. 35 Tahun 2009 dan Pedoman Jaksa Agung No. 11 Tahun 2021, sistem penegakan hukum dibangun dengan diferensiasi pelaku, di mana penyalahguna, pecandu, dan korban penyalahgunaan diarahkan pada mekanisme rehabilitatif, sedangkan pengedar, pembuat, kurir, dan pelaku jaringan ditindak melalui pendekatan represif. Asesmen Terpadu menjadi instrumen kunci untuk menentukan status pelaku secara medis dan yuridis, sehingga mencegah kriminalisasi berlebihan dan memastikan respons hukum yang tepat. Penelitian ini menunjukkan bahwa efektivitas penegakan hukum sangat bergantung pada konsistensi penerapan asesmen, profesionalitas aparat, serta koordinasi lintas-instansi. Kesimpulannya, model penegakan hukum narkotika Indonesia telah mengintegrasikan perlindungan HAM, keadilan substantif, dan penindakan terhadap ancaman peredaran gelap, sekaligus menempatkan asesmen sebagai penyaring utama dalam menentukan jalur penanganan perkara.